2014
DOI: 10.1371/journal.pone.0095204
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Ionized Calcium in Critically Ill Patients: An Analysis of a Large Clinical Database MIMIC II

Abstract: Background and Objectiveionized calcium (iCa) has been investigated for its association with mortality in intensive care unit (ICU) patients in many studies. However, these studies are small in sample size and the results are conflicting. The present study aimed to establish the association of iCa with mortality by using a large clinical database.MethodsMultiparameter Intelligent Monitoring in Intensive Care II (MIMIC II) database was used for analysis. Patients older than 15 years were eligible, and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 29 publications
3
64
0
2
Order By: Relevance
“…Our findings are supported by a previous study, which reported that the incidence rates of moderate hypocalcemia (ionized calcium less than 0.9 mmol/L) and hypercalcemia (ionized calcium more than 1.35 mmol/L) were 10.8% and 6.7%, respectively . The increased rate of abnormal ionized calcium in critical illness may be due to the following: (i) increased urine or fecal calcium excretion; (ii) decreased intake of dietary calcium and vitamin D, a promoter of calcium absorption in the intestine; (iii) underlying diseases or comorbidities affecting calcium homeostasis, such as sepsis and renal failure; and (iv) medication side effects, such as parathyroid surgery, catecholamine administration, and transfusion of citrated blood.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are supported by a previous study, which reported that the incidence rates of moderate hypocalcemia (ionized calcium less than 0.9 mmol/L) and hypercalcemia (ionized calcium more than 1.35 mmol/L) were 10.8% and 6.7%, respectively . The increased rate of abnormal ionized calcium in critical illness may be due to the following: (i) increased urine or fecal calcium excretion; (ii) decreased intake of dietary calcium and vitamin D, a promoter of calcium absorption in the intestine; (iii) underlying diseases or comorbidities affecting calcium homeostasis, such as sepsis and renal failure; and (iv) medication side effects, such as parathyroid surgery, catecholamine administration, and transfusion of citrated blood.…”
Section: Discussionsupporting
confidence: 90%
“…Among these three states, only ionized calcium is physiologically relevant, and critically high or low ionized calcium is life‐threatening . Indeed, previous studies concluded that extremely low or high ionized calcium is independently associated with hospital mortality in adult patients admitted to the intensive care unit (ICU) …”
Section: Introductionmentioning
confidence: 99%
“…The aim of the acute management isn't only to return the serum calcium to the normal level but rather to ameliorate the acute manifestations of hypocalcemia [16] which have a direct impact on patient's daily life. Some studies concluded that moderate hypocalcemia has an increased incidence of mortality compared to mild hypocalcemia [17]. Moreover, a large retrospective study showed that calcium supplementation during the ICU stay improved 28-day survival in critically ill adult patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast other studies have concluded thath both mild and moderate hypocalcemia are associated with increased mortality. One large retrospective study showed that callcium supplementation improved 28 day survival in the ICU in critically ill patients [45,46].…”
Section: Treatment Correcting Hypocalcemiamentioning
confidence: 99%